Concept of metallic magnetic calorimeters for rare event search in the LUMINEU project - Loidl, Martin; Rodrigues, M.; Navick, X. -F.; Fleischmann, Andreas; Gastaldo, Loredana; Enss, Christian (Journal of low temperature physics, 2014)
The project LUMINEU is mainly aiming at the search for neutrinoless double-beta decay of the candidate nuclide $$^{100}$$100Mo using cryogenic ZnMoO$$_4$$4detectors with simultaneous heat and scintillation light detection for radioactive background rejection. It also includes some development for dark matter search using cryogenic Ge detectors with simultaneous heat and ionization detection for background rejection. For both cases, metallic magnetic calorimeters (MMCs) are studied among several thermometer types. In double-beta decay search, the intrinsically fast response of MMCs reading out the light detector may allow for a very fast signal rise time and help to reduce the potential background due to pile-up of two-neutrino double beta decay events. In dark matter search, MMCs reading out the heat channel may improve the energy resolution with respect to the standard NTD Ge thermistor readout and hence the sensitivity of the detectors for low-mass WIMPs.
Published online: 25 December 2013
Gesehen am 27.07.2020